Disease severity and prefrontal cortex activation during obstacle negotiation among patients with Parkinson's disease: Is it all as expected?. (August 2022) - Assad, M.; Galperin, I.; Giladi, N.; Mirelman, A.; Hausdorff, J.M.; Maidan, I.
Abstract: Background: Previous reports indicate that patients with Parkinson's disease (PD) activate the prefrontal cortex (PFC) during complex activities such as obstacle negotiation to compensate for impaired motor function. However, the influence of disease severity on PFC activation has not been systematically evaluated. Here, we examined the effects of disease severity on PFC activation during obstacle negotiation. Methods: 74 patients with PD (age 68.26 ± 7.54 yrs; 62.2% men) were divided into three groups based on Hoehn and Yahr stages. All patients walked along an obstacle course while negotiating anticipated and unanticipated obstacles (long/low available response time) at heights of 50 mm and 100 mm. PFC activation was measured using functional near-infrared spectroscopy (fNIRS) and was compared between groups and tasks using mixed model analyses. Results: Participants with more advanced PD (i.e., Hoehn & Yahr 3) had higher PFC activation levels when negotiating anticipated obstacles, compared to participants with milder PD (i.e., Hoehn & Yahr 1, 2) (p < 0.001). Moreover, higher LEDD correlated with higher prefrontal activation during the higher anticipated obstacle. In contrast, during the negotiation of unanticipated obstacles, the differences in PFC activation were not associated with disease severity in a linear manner. Conclusions: The present study suggests that with increased disease severity, patients with PD rely more on the PFC when negotiating anticipated obstacles, perhaps to compensate for attention and motor deficits. These findings support the role of cognition in fall risk and the need to improve attention and cognition in fall prevention programs, especially among patients with more advanced disease. Highlights: The effects of obstacle suddenness on PFC activation depend on disease severity. PFC activation increased during anticipated obstacle negotiation as a function of PD severity. PFC activation during unanticipated obstacles were not associated with disease severity in a linear matter. LEDD correlated to PFC activation while crossing high-anticipated obstacles.